Current progress in CAR-based therapy for kidney disease - Zhang, Dan; Sun, Dong (Frontiers in Immunology, 2024)
proportion of patients exhibit poor responses to current therapies or have been categorized as refractory renal disease. Engineered T cells have emerged as a focal point of interest as a potential treatment strategy for kidney diseases. By genetically modifying T cells and arming them with chimeric antigen receptors (CARs), effectively targeting autoreactive immune cells, such as B cells or antibody-secreting plasma cells, has become feasible. The emergence of CAR T-cell therapy has shown promising potential in directing effector and regulatory T cells (Tregs) to the site of autoimmunity, paving the way for effective migration, proliferation, and execution of suppressive functions. Genetically modified T-cells equipped with artificial receptors have become a novel approach for alleviating autoimmune manifestations and reducing autoinflammatory events in the context of kidney diseases. Here, we review the latest developments in basic, translational, and clinical studies of CAR-based therapies for immune-mediated kidney diseases, highlighting their potential as promising avenues for therapeutic intervention.